Model driven development and its use in the development of large information systems - Barchánková, Adéla (2020)
The main aim of this bachelor thesis is to provide a comprehensive description of Model-driven development and analyse its approaches, practices and available tools with focus on server-based applications of large information systems. The first part of this study shall cover the definitions of the methodology, its principles, best practices, and analyse the possible benefits or disadvantages of this approach. It will also capture the current situation on the market with commercial MDD tools. Second part contains an analysis and description of the Metasystem application: a non-commercial MDD tool developed by Czech IT company, which is used for modelling and development of large information systems. The thesis provides a comparison between the mentioned tool and one of the most commonly used application – Sparks’s Enterprise Architect with one main question: Would Metasystem be commercially competitive on current market? In the latter part, the thesis focuses on an analysis and design of possible enhancements in the functionality of the tool.